(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
Activated carbon is commonly used in water and wastewater treatment, removing organics that cause unpleasant odors, tastes and other detrimental effects. In this study, bioremediation treatment consists of biofilms of two types of microbes, i.e. Bacillus sp and Escherichia sp are grown and immobilized on the Mukah coal activated carbon from Sarawak. Prepared activated carbon was categorized by different physical geometries design such as SGAC I, SGAC II, SGAC III, HCGAC I, HCGAC II and HCGAC III. The target pollutants to be removed from the Ramatex textile wastewater were BOD5, COD, TSS, color, phosphate, nitrate and sulfate.Â Escherichia sp with SGAC I was found to give the best results for the bioremediation process and the percentage of BOD5, color,COD,TSS, nitrate, sulfate and phosphate removal were 71.4%, 91.1%, 96.4%, 98.8%, 80.3%, 90.3% and 60.3% respectively. The results indicated that combination between physical and biological treatment was the main factor for the best pollutants removal achievement.